2018
DOI: 10.1021/jacs.8b11667
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Platinum Catalysts for Nitrile and Cyanohydrin Hydration: Catalyst Design and Ligand Screening via High-Throughput Techniques

Abstract: Nitrile hydration provides access to amides that are indispensable to researchers in chemical and pharmaceutical industries. Prohibiting the use of this venerable reaction, however, are 1) the dearth of biphasic catalysts that can effectively hydrate nitriles at ambient temperatures with high turnover numbers, and 2) the unsolved challenge of hydrating cyanohydrins. Herein, we report the design of new "donor-acceptor"-type platinum catalysts by precisely arranging electron-rich and electron-deficient ligands t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 38 publications
0
59
0
1
Order By: Relevance
“…There has been signicant recent interest in the development of nitrile hydration catalysts based on transition metals, but most systems reported to date still require relatively high temperatures to reach appreciable catalytic turnover. 7 Recent progress with Rh(I), 8 Ru(II), 9 Pd(II), 10 and Pt(II) 11 catalysts has allowed catalytic nitrile hydration under mild conditions, but additives are oen required for high activity (e.g., AgOTf in Grubbs' Pt(II)/phosphinous acid catalysts, 11 or Sc(OTf) 3 in Yin's Pd(II) catalysts 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been signicant recent interest in the development of nitrile hydration catalysts based on transition metals, but most systems reported to date still require relatively high temperatures to reach appreciable catalytic turnover. 7 Recent progress with Rh(I), 8 Ru(II), 9 Pd(II), 10 and Pt(II) 11 catalysts has allowed catalytic nitrile hydration under mild conditions, but additives are oen required for high activity (e.g., AgOTf in Grubbs' Pt(II)/phosphinous acid catalysts, 11 or Sc(OTf) 3 in Yin's Pd(II) catalysts 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…With complex RuCl 2 (PTA) 4 ,t he studies were conducted in ap H6.8 buffer and compared to the previously reportedd ata in water (Table 7). [46] Our group have reported that [(h 6 -arene)RuCl(k 2 -PTA-CPh 2 NHPh)]Cl can reach TOF of 285 h À1 at 100 8Cf or the hydration of benzonitrile;h owever, significant catalyst decomposition was observed under our reactions conditions. The RuCl 2 (PTA) 4 catalyst reacts faster than the in situ generated catalyst in both solvents ystems.…”
Section: Temperature Studiesmentioning
confidence: 61%
“…[45] Theh ydration of acetonitrile in tetrahydrofuran/water was reportedt oh ave aT OF of 318 h À1 at 40 8C( turnover number (TON) = 12 712) using [(DPPF)PtCl(PMe 2 OH)]OTf as the catalyst. [46] Our group have reported that [(h 6 -arene)RuCl(k 2 -PTA-CPh 2 NHPh)]Cl can reach TOF of 285 h À1 at 100 8Cf or the hydration of benzonitrile;h owever, significant catalyst decomposition was observed under our reactions conditions. [31] Other systemss uch as [(h 6 -arene)R-uCl 2 P(NMe 2 ) 3 ]h ave shown impressive reactivity and are synthe- sized from commercially available materials with TOF up to 11 400 h À1 using microwave( MW) irradiation (150 8C).…”
Section: Temperature Studiesmentioning
confidence: 61%
See 2 more Smart Citations